Molecular simulation of the damage tolerance of NiCoCr medium-entropy alloys with a cavity under uniaxial tension - Leow, Peng Soon (Nanyang Technological University, 2024)
This project delves into the damage tolerance of the NiCoCr medium entropy alloy, specifically in the presence of a cavity defect, utilizing molecular dynamic simulations. The investigation encompassed two series of tensile tests on the alloy. The first set scrutinized the impact of different grain sizes, while the second set explored the influence of various strain rates. The study discerned that larger grain sizes tended to diminish alloy strength, with a notable anomaly. A parallel trend was identified with higher strain rates. Thorough analyses of the alloy's strength and dislocation densities were conducted under these diverse conditions, culminating in conclusions regarding the alloy with the most favorable properties.